Educação para empreender: um estudo da relação entre práticas didáticas, aprendizagem e intenção empreendedoras - Bürger, Rafaela Escobar (2018)
his study aimed to analyze the process of entrepreneurial education and its stimulus for the development of entrepreneurial intention in undergraduate students of an institution of higher education, considering their didactic practices and entrepreneurial learning. A qualitative and quantitative, exploratory, descriptive study was carried out based on theoretical-empirical research and data triangulation. In the qualitative approach, interviews with semi structured scripts were carried out with students and professors of the subjects of Entrepreneurial Attitude of UFSM. To analyze the interviews, the content analysis method was used (BARDIN, 2014). The categories of analysis defined a priori were: didactic practices, entrepreneurial learning and entrepreneurial intention. In the quantitative approach, the data were collected through the application of the Questionnaire of Entrepreneurial Intention, developed by Liñán and Chen (2009) in the students of that disciplines. As a result, from the reports, it was possible to identify the use of eleven (11) didactic practices, divided into the subjects of Entrepreneurial Attitude. From the evidenced didactic practices, one can perceive abilities developed in the students such as: Sensitization / vision, opportunity search, planning, critical sense, strategy, initiative / proactivity, risk taking, innovation, leadership and motivation. In addition to these characteristics cited by the students, others were evidenced from the interpretation of the lines, such as: Entrepreneurial behavior and personal development. In addition, the results of the quantitative stage showed that the means of the QIE factors in the collection at the end of the course were higher than those found at the beginning. The association of the two approaches was performed by the data triangulation technique. The relationship between the skills developed from the entrepreneurial learning process and the relevant behaviors and raised in each of the questions of the Entrepreneurial Intent (EI) were analyzed. As a result, it can be observed that the didactic practices adopted have effectively generated positive results in the students and are evidenced by the development of the skills, perceived by the students through their reports and the instrument for the measurement of the entrepreneurial intention, and by the researcher based on the analysis performed. As limitations of this research, it can not be said categorically that the results found here were exclusively the didactic practices used by the teachers. As well as, it can not be said categorically that what was developed was due to the discipline, however, the results found make it clear that the practices and the disciplines, in fact, contributed to this development As a suggestion for future studies, it is expected that research in this sense will occur continuously in higher education institutions, allowing to verify the evolution and development of both students 'and teachers' behavior.